GE_GERICHTE P/16588/2020 vom 23. Juli 2022 - GE Cour de justice (2022)
COCAÏNE;VENTE;COAUTEUR(DROIT PÉNAL);PARTICIPATION OU COLLABORATION;EXPULSION(DROIT PÉNAL) | LStup.19.al1.letg; LStup.19.al1.leta; Lstup.19.al2; CP.66a.al1.leto